The keratinolytic bacteria Bacillus cytotoxicus as a source of novel proteases and feather protein hydrolysates with antioxidant activities - Cavello, Ivana Alejandra (2021)
Background: Argentina’s geothermal areas are niches of a rich microbial diversity. In 2020, species of Bacillus cytotoxicus were isolated for the first time from these types of pristine natural areas. Bacillus cytotoxicus strains demonstrated the capability to grow and degrade chicken feathers with the concomitant production of proteases with keratinolytic activity, enzymes that have multitude of industrial applications. The aim of this research was to study the production of the proteolytic enzymes and its characterization. Also, feather protein hydrolysates produced during fermentation were characterized. Results: Among the thermotolerant strains isolated from the Domuyo geothermal area (Neuquén province, Argentina), Bacillus cytotoxicus LT-1 and Oll-15 were selected and put through submerged cultures using feather wastes as sole carbon, nitrogen, and energy source in order to obtain proteolytic enzymes and protein hydrolysates. Complete degradation of feathers was achieved after 48 h. Zymograms demonstrated the presence of several proteolytic enzymes with an estimated molecular weight between 50 and > 120 kDa. Optimum pH and temperatures of Bacillus cytotoxicus LT-1 crude extract were 7.0 and 40 °C, meanwhile for Oll-15 were 7.0 and 50 °C. Crude extracts were inhibited by EDTA and 1,10 phenanthroline indicating the presence of metalloproteases. Feather protein hydrolysates showed an interesting antioxidant potential measured through radical-scavenging and Fe3+-reducing activities. Conclusion: This work represents an initial approach on the study of the biotechnological potential of proteases produced by Bacillus cytotoxicus. The results demonstrated the importance of continuous search for new biocatalysts with new characteristics and enzymes to be able to cope with the demands in the market.